x=70-2•[16•6+2•(16•3+72:16)-36]:12
Răspunsuri la întrebare
Răspuns de
1
X=70-2•[16•6+2•(16•3+72:16)-36]:12
X=70-2•[96+2•(48+4,5)-36]:12
X=70-2•(96+2•52,5-36):12
X=70-2•(96+105-36):12
x=70-2•165:12
x=70-27,5
x=42,5
X=70-2•[96+2•(48+4,5)-36]:12
X=70-2•(96+2•52,5-36):12
X=70-2•(96+105-36):12
x=70-2•165:12
x=70-27,5
x=42,5
Răspuns de
2
.....................................
Anexe:
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă